The Effect of Diversification on Tail Risk: Evidence from US Equity Mutual Fund Portfolios. (25th February 2016) - Xu, Simon; Hwang, Inchang; In, Francis
Abstract: This paper examines the effect of diversification on the tail risk of US equity mutual fund portfolios by utilizing classical higher‐moment measures and robust tail weight measures. Empirical results show that market standard portfolios based on the mean‐variance framework are exposed to greater tail risk than benchmark portfolios are and diversification further intensifies this exposure.